Integration of Customary Law in The National Legal System Comparative Study of Malaysia and Indonesia - Febrianty, Yenny; Ghapa, Hasliza; Ahmad, Asmida (SASI, 2024)
Introduction: Customary law shapes and protects indigenous cultural identity and rights in the face of rapid modernity. However, customary law incorporation into national legal systems, notably in Malaysia and Indonesia, remains difficult. Both nations recognize and integrate customary law into their legal systems, but disparities in indigenous peoples' land, forestry, and natural resource management rights enforcement and protection exist.Purposes of the Research: The study's main objectives are to (1) understand and evaluate customary law's inclusion into Malaysia and Indonesia's legal systems and (2) determine the best framework for this incorporation given the fast rate of modernization.Methods of the Research: This research employs a normative juridical methodology with statutory and comparative approaches. Through a review of relevant laws and literature from both countries, this study seeks to identify and compare how customary law is integrated into the national legal systems of Malaysia and Indonesia.Results of the Research: The research identified discrepancies in indigenous peoples' rights enforcement and protection, notably in land, forestry, and natural resource management, despite both countries adopting customary law into their legal systems. This research emphasizes the necessity for inclusive and participatory customary law incorporation into national legal systems. Customary law is important to these systems and is acknowledged, preserved, and respected. Scholars, attorneys, and legislators in both countries may utilize this study to protect indigenous rights.